Efficiency of Katarungang Pambarangay in Resolving Domestic Dispute at Barangay Kaligayahan, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research aimed to evaluate the efficiency of Katarungang Pambarangay inresolving domestic disputes in Barangay Kaligayahan, Quezon City. The study utilized adescriptive research method and involved the participation of 50 respondents, including 20Barangay Personnel and 30 Barangay Residents, selected through purposive sampling. Themajor instrument for data gathering was a survey questionnaire that employed a percentageformula, ranking, weighted mean, and Likert scale to determine the efficiency of KatarungangPambarangay.The results of the study showed that the efficiency of Katarungang Pambarangay in resolvingdomestic disputes at Barangay Kaligayahan, Quezon City, was perceived as "very effective"by the respondents in terms of settlement, enforcing law, and Barangay assistance. However,some problems encountered during the proceedings, such as non-attendance of respondentsand complainants, lack of knowledge about their rights, and disobedience of commands byBarangay officials, were also identified. The respondents suggested that the Barangayofficials should undergo training and seminars to become more effective in their duties.To address the issues encountered in barangay proceedings, a multi-pronged approach isrecommended. Clear communication, follow-up measures, and education about rights andresponsibilities should be provided to all parties involved. Providing training and resources forbarangay officials and regularly assessing their performance is also important.
Keywords: Criminology